Population and food supply: the challenge for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Africa now needs 14 million tonnes more grain each year than it is producing. With the population growing at three percent per year and agricultural production increasing by only two percent, that shortfall will reach 50 million tonnes by 2000. How...